Strategic Environmental Assessment: a contribution to sustainability of tourism development - Jiliberto Herrera, Rodrigo Alejandro (2015)
The Strategic Environmental Assessment (SEA) is a consolidated environmental policy tool at international level. The state of the art shows that despite its increasing application at international level some conceptual aspects remain still open and condition its praxis. We argue here that the problem roots in the lack of a precise identification of the SEA’s own object of analysis differentiated from the one of its predecessor, the environmental impact assessment of projects. We propose in this article a definition of the SEA specific object of analysis, and illustrate its application in the SEA of tourism development policies.